Manajemen Laba dalam Sudut Pandang Etika Bisnis Islam - Indah Muliasari; Dalili Dianati (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2014)
Earnings management in this study are based on the opinion of Schipper that saidearnings management as managerial engineering undertaken by management to deliberately intervene in the process of determining earnings or financial reporting by utilizing techniques and accounting policy for a particular purpose. This study aims to examine and analyze the point of view of Islamic business ethics on the practice of earningsmanagement. This study used a qualitative descriptive methods, data collection technique, study of literatures and interviews. The results showed that earnings managementis not in accordance with Islamic business ethics. Islamic business ethics contains thevalues of tauhid, unity; fair, equilibrium; freedom; responsibility; ihsan, benevolence.